Glucolipotoxicity: A Proposed Etiology for Wooden Breast and Related Myopathies in Commercial Broiler Chickens - Lake, Juniper A.; Abasht, Behnam (Frontiers in Physiology, 2020)
Wooden breast is one of several myopathies of fast-growing commercial broilers that has emerged as a consequence of intensive selection practices in the poultry breeding industry. Despite the substantial economic burden presented to broiler producers worldwide by wooden breast and related muscle disorders such as white striping, the genetic and etiological underpinnings of these diseases are still poorly understood. Here we propose a new hypothesis on the primary causes of wooden breast that implicates dysregulation of lipid and glucose metabolism. Our hypothesis addresses recent findings that have suggested etiologic similarities between wooden breast and type 2 diabetes despite their phenotypic disparities. Unlike in mammals, dysregulation of lipid and glucose metabolism is not accompanied by an increase in plasma glucose levels but generates a unique skeletal muscle phenotype, i.e. wooden breast, in chickens. We hypothesize that a major difference between birds and mammals in glucose transport is responsible for these phenotypic disparities. Additional basic research on wooden breast and related muscle disorders in commercial broiler chickens is necessary and can be informative for poultry breeding and production as well as for human health and disease. To inform future studies, this paper reviews the current biological knowledge of wooden breast, outlines the major steps in its proposed pathogenesis, and examines how selection for production traits may have contributed to its prevalence.